1990
DOI: 10.1080/00288330.1990.9516404
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthic community composition of six intertidal sandflats in Manukau Harbour, New Zealand

Abstract: Macrobenthic community structure was assessed on intertidal sandflats, apredominant feature of Manukau Harbour. Thirty-six replicate core samples were collected from each of six 9000 m 2 sites, during October 1987. The distribution of individuals amongst taxa was similar at the six sites, but the numerical dominance of the most common taxa changed appreciably from site to site. A shift from polychaete-to bivalve-dominated communities was apparent between sites. Examination of a hypothesised relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…The sampling design and its justification are presented in detail in Pridmore et al (1990). Hewitt et al (1993) and Thrush et al (1994).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sampling design and its justification are presented in detail in Pridmore et al (1990). Hewitt et al (1993) and Thrush et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…Extensive intertidal sand-flats are a major feature of the Harbour, comprising about 4 0 % (145 km2) of its area. The macrobenthic infaunal communities of these sand-flats play an important role in the overall ecology of the Harbour (Pridmore et al 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface sediments comprise 0-3% gravel (primarily shell hash), 92-97% sand, and 3.5% mud by dry weight. The macrofaunal community is dominated in terms of both abundance and biomass by bivalves (Pridmore et al, 1990).…”
Section: Study Sitementioning
confidence: 99%
“…Time-series data demonstrate that macrofaunal communities have been remarkably persistent over recent years (Turner et al, 1995). The most relevant descriptions of the Wiroa Island sandflat macrofaunal community are given in Cassie and Michael (1968) and Pridmore et al (1990). Studies of sedimentary processes have shown that sediment entrainment by strong spring tidal currents is restricted to the lower regions of the intertidal sandflat, while episodic wind-waves ( # 0.7 m in height) dominate sediment resuspension in the upper intertidal reaches (Dolphin et al, 1995).…”
Section: Previous Workmentioning
confidence: 99%